Complete whole genome sequencing of Vibrio parahaemolyticus strain UMP001VA, isolated from sea cucumber Holothuria leucospilota from Malaysia harbouring blaCARB-33 gene - Choo, Mei Yen; Siew, Shing Wei; Najatul Su-Ad, Abdullah; Mohd Azrul Naim, Muhammad; Hajar Fauzan, Ahmad (Elsevier Ltd, 2023)
Pathogenic strain of Vibrio parahaemolyticus found in marine and coastal ecosystems can cause infections in marine animals. Increasing antibiotic resistance reported in Vibrio species may be linked to environmental contamination. Here, we present a 4.99-Mbp complete genome sequence of V. parahaemolyticus strain UMP001VA, a Gram-negative bacterium that was isolated from the gut content of a sea cucumber Holothuria leucospilota collected from Pulau Rhu, Terengganu, Malaysia. The whole genome sequencing was performed using hybrid de novo assembly using Illumina and the Oxford Nanopore Technology platforms. The genome analysis reported a total length of 4,991,208 bp of V. parahaemolyticus genome sequences with 45.3 % GC content. The functional annotation of the genome showcased that 56 genes of V. parahaemolyticus were associated with virulence, disease, and defence function. Virulence factors found in H. leucospilota were related to T3SS1, together with the presence of blaCARB-33 antibiotic resistance gene conferring ampicillin, piperacillin, and amoxicillin drug resistance were reported. The presence of virulence factors and antibiotic resistance genes reveals the considerable pathogenic potential of V. parahaemolyticus in sea cucumbers. Therefore, the whole genome sequencing presented here provides a fundamental genome insight for future assessment of V. parahaemolyticus in marine organisms.